Hubungan Komunikasi Terapeutik Perawat Dengan Kecemasan Pasien Pre Operasi - Sony Wahyu Tri Cahyono (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Introduction Anxiety from surgery is something that is often experienced by someone, here the role of the operating room nurse is how to reduce the anxiety level of preoperative patients, including by applying therapeutic communication to preoperative patients. The purpose of this study was to determine the relationship between nurse therapeutic communication and preoperative patient anxiety. Methods The research design uses the Correlational Research Method with a Cross Sectional approach. The population of this study are patients who will undergo surgery. The research sample used Accidental Sampling and obtained a sample of 58 patients from a population of 86 patients. Data collection used the HARS questionnaire. Statistical Test Spearman rank statistical test with α (0.05) SPSS 20. Results The results of this study showed that most of the 42 respondents (72.42%) had good therapeutic communication criteria and almost all 47 respondents (81.03%) had moderate anxiety criteria. The results of the Spearman rank statistical test analysis obtained p value = 0.008, which means there is a relationship between nurse therapeutic communication and preoperative patient anxiety. Discussion Communication is an action that is the application of the nurse's duties as a counselor and educator. Therapeutic communication in nursing needs to be developed to provide education and psychological support for patients who will undergo an action that the patient has never undergone, such as surgery.